Postnatal microcephaly and pain insensitivity due to a de novo heterozygous DNM1L mutation causing impaired mitochondrial fission and function. Issue 6 (17th March 2016) - Sheffer, Ruth; Douiev, Liza; Edvardson, Simon; Shaag, Avraham; Tamimi, Khaled; Soiferman, Devorah; Meiner, Vardiella; Saada, Ann
Abstract : An emerging class of mitochondrial disorders is caused by mutations in nuclear genes affecting mitochondrial dynamics and function. One of these is the DNM1L gene encoding the dynamin‐related protein 1 (DRP1), which is pivotal in the mitochondrial fission process. Here, we describe a patient with a novel dominant‐negative, de novo DNM1L mutation, which expands the clinical spectrum. The patient reported here exhibits a chronic neurological disorder, characterized by postnatal microcephaly, developmental delay, and pain insensitivity. Muscle biopsy disclosed decreased respiratory chain complex IV activity. Exome sequencing showed a de novo heterozygous c.1084G>A (p.G362S) mutation. Subsequent studies of patient skin fibroblasts showed markedly impaired mitochondrial fission and a partial respiratory chain defect while peroxisomal morphology remained intact. Human foreskin fibroblasts over‐expressing the mutant DNM1L gene displayed aberrant mitochondrial morphology. © 2016 Wiley Periodicals, Inc.